THE IMPACT OF COVID-19 PANDEMIC ON THE MANAGEMENT OF UMRAH PACKAGE OPERATIONS IN MALAYSIA - Mahmad, Muhamad Amar; Ismail, Nor Hanani; Rofie, Mohamad Khadafi bin Hj.; Ahmad, Shukri (CENTRAL ASIA AND THE CAUCASUS, 2024)
Umrah package operations in Malaysia have recorded a significant increase every year. Before leaving for Umrah, Muslims need to make various preparations including travel, operations, and worship. So far, the management of umrah operations must adhere to the MPPU requirements. Nevertheless, this management manual still fails to produce quality management standards in monitoring the entire operation of umrah packages in Malaysia. Some problems such as the misuse of operating licenses, taking excessive profits, and handling of unregistered packages still occur. However, the 2019 Coronavirus pandemic (Covid-19) global outbreak has resulted in many countries implementing travel restrictions and movement controls. In Malaysia, the business sector is one of the sectors directly affected by the movement control order (MCO). In summary, using the qualitative and quantitative methods, the findings of the study found that covid-19 had a significant impact on umrah operators. Therefore, it is hoped that improvement in the assistance provided can ensure the continuity of their business.